The Use of Metaphor and Symbolism In BTSâ€™s Black Swan Song - Maharani, Carissa; Djauhari, Otong Setiawan (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article discusses metaphors contained in a song as an expression of the songwriter's emotions about something that happened in their real life. BTS's single â€œBlack Swanâ€ contains metaphorical elements in its lyrics. The author will explain the use of metaphors in one of BTS's popular singles, â€œBlack Swan.â€ In this study, the author employs a qualitative descriptive research method. According to Nasution, qualitative research is a research procedure that generates descriptive data from observed individuals and behaviors. This study aims to collect as much descriptive data as possible to be organized in a report and analysis. According to the analysis conducted, only three types of metaphors were found: ontologycal, structural, and orientational. Now we will discuss each type of metaphor in the BTS song â€œBlack Swanâ€ in detail: These three types of metaphors not only enrich the language and poetic nuances of the song but also help listeners understand the inner conflict and identity transformation experienced by the narrator. This analysis demonstrates that the lyrics of â€œBlack Swanâ€ are not merely an entertainment product but an artistic expression rich in philosophical and psychological meaning, making it worthy of study in the fields of literature and linguistics.